(The Study of Making Bamboo Charcoal and Vinegar using Pyrolisis Kiln of Semi Commercial Scale) - Pohan, H.G; Wijaya, Hendra; Suherman, Ade (Balai Besar Industri Agro, 2010)
Study on production of bamboo charcoal an vinegar have been carried out semi commercially using pyrolysis furnace with a volume of 6 m3. The result of this study is expected to be a model of processing bamboo charcoal and vinegar for rural area. Observations were made on the characteristics of pyrolysis, yield of charcoal and bamboo vinegar, and characteristics of charcoal i.e., water content, ash, volatile matter, fixed carbon, calories, and pH. The bamboo raw material availability and techno-economical analysis were also conducted. The study revealed that the temperature of the out coming gar during the pyrolization process was 300 to 350 oC, the average yield of charcoal and vinegar were 27.33% and 33.61% respectively. The resulted bamboo charcoal has water content of 3.06%, volatile matter at 950oC was 40.03% (wb), ash content was 7.2% (wb), fixed carbon of 52.37% (wb) and calorific value of 5777 cal/g. The resulted bamboo vinegar has pH 4 and its refractive index was ranged from 3.25 - 3.75. The availability of raw material bamboo in the Village at Desa Tenjojaya, Kecamatan Cibadak Kabupaten Sukabumi, within the radius of 4 km was 3620 ton, while the possible selling price of the resulted charcoal was Rp. 3.000.-/kg whereas the vinegar was Rp.5000.-/kg. The techno-economical analysis of the processing unit of bamboo charcoal and vinegar with the capacity of 10 tons of charcoal per month revealed Present Value (NPV) of Rp.596.000.000,-, the Internal Rate pf Return (IRR) of 78% or Pay-back period was 1.3 years.